2012
DOI: 10.1111/j.1471-4159.2012.07845.x
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin associated protein 1 regulates trafficking of the amyloid precursor protein and modulates amyloid beta levels in neurons

Abstract: J. Neurochem. (2012) 122, 1010–1022. Abstract Amyloid precursor protein (APP) is involved in the pathogenesis of Alzheimer’s disease. It is axonally transported, endocytosed and sorted to different cellular compartments where amyloid beta (Aβ) is produced. However, the mechanism of APP trafficking remains unclear. We present evidence that huntingtin associated protein 1 (HAP1) may reduce Aβ production by regulating APP trafficking to the non‐amyloidogenic pathway. HAP1 and APP are highly colocalized in a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 62 publications
(135 reference statements)
1
18
0
Order By: Relevance
“…The biotinylation assay for APP and BACE1 was performed as previously described (Yang et al . ). Briefly, cortical neurons from P0 p75 −/− and p75 +/+ mice were isolated and cultured in six‐well plates.…”
Section: Methodsmentioning
confidence: 97%
“…The biotinylation assay for APP and BACE1 was performed as previously described (Yang et al . ). Briefly, cortical neurons from P0 p75 −/− and p75 +/+ mice were isolated and cultured in six‐well plates.…”
Section: Methodsmentioning
confidence: 97%
“…Lactadherin amyloid, a deposit known as medin that is localized in aortic medium, occurs in virtually all individuals older than 60 years. The huntingtinassociated protein 1 modulates the A␤PP subcellular trafficking pathway, thus negatively regulating A␤ production in neurons (78). Loss of superoxide dismutase (SOD) increases production of A␤ in neurons and SHSY5Y cells, an effect caused by enhanced A␤PP processing by the ␤-site A␤PP-cleaving enzyme (79), whereas earlier studies have shown that overexpression of superoxide dismutase reduces A␤ neurotoxicity (80).…”
Section: Other Amyloid Proteinsmentioning
confidence: 99%
“…Since APP is cleaved by various secretases during its trafficking within the cell, identifying proteins that can regulate APP transport and thus affect its processing for Aβ generation may shed light on elucidating the pathogenesis of AD. Recent studies have identified multiple APP-interacting proteins, such as Mints[13], LRP[14,15], RanBP9[16], SorLA/LR11[17,18], AP-4[19], FBL2[20], APLP1[21], SNX17[22], ApoER2[23], HAP1[24] and flotillin-2[25], that can regulate APP trafficking and Aβ generation.…”
Section: Introductionmentioning
confidence: 99%